Operators Need to Know Basic Microbiology. Issue 7 (3rd September 2021) - Adams, Hunter; Reeder, Sam; Barker, Randall; Ash, Steve; Williams, Kriston; Southard, Mark
Abstract : The data produced in water treatment plants contain a wealth of information on how well processes perform, but the key is how well the information is understood and applied. With a fundamental knowledge of microbiology and chemistry, plant operators are better equipped to get the most out of test results to help ensure high‐quality water.